Infrared transmittance model for pyrometric monitoring of surface quality of thin diamond films - Kulesza, Sławomir (Surface & coatings technology, 2012)
The thickness and surface roughness of thin diamond films grown on quartz substrates are studied in the paper using a model of changes in the infrared transmission ratio associated with multiple constructive interference within a thin crystal film. On the other hand, the model is referred to periodic variations of the apparent temperature of the substrate measured by the two-color pyrometer. Obtained results are then compared with those of other similar studies, and the AFM measurements. Some discrepancy between the results from infrared and AFM data is explained in terms of optical absorption of the crystal, which is neglected in the transmittance model. ► The model of the infrared transmittance of thin films in surrounding media. ► Extraction of the film thickness and surface roughness from the measured temperature. ► Reasonable agreement between the results on the roughness extracted from the model, and the AFM data. ► Delamination of the film observed in the roughness data.